Lecturer’s Performance Supported by Lecture’s Ambitious and Commitment - Kusumawati, Erna; Yunaningsing, Ani; Febriani, Reni; Kurnianingrum, Dian; Alamsyah, Doni Purnama (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to review the impact of teachers’ commitment and ambitious on the improvement of teachers’ performance. The study is conducted in Jakarta, with the sample taken of 120 teachers who have certified as teachers. Data from teachers taken through questionnaires and processed by Lisrel; it is also conducted research hypothesis test. Research results are stated that teachers’ ambitious and commitment can truly control teachers’ performance. Furthermore, the ambition has a better impact on improving teachers’ performance than commitment. This study is useful as input for headmasters and government in developing ambitiousness-soul to improve teachers’ performance besides commitment as a teacher.